Determination of Cost-Effective Sand Mixing Ratio for Improvement of High Liquid Limit Soil Based on Fuzzy Comprehensive Evaluation. Issue 3 (November 2021) - Sun, Dongning; Liu, Xin; Cao, Yuhao; Gong, Junjie; Hong, Baoning
Abstract: In order to save soil resources and increase the utilization range of high liquid limit soil, the high liquid limit soil was improved by mixing sand, and the cost-effective sand mixing ratio was determined with the help of fuzzy comprehensive evaluation method. It is shown that the sand-mixing improvement method can significantly reduce the liquid limit and plasticity index of high liquid limit soil, and increase its value of California bearing ratio to meet the property requirements for embankment filling. The fuzzy comprehensive evaluation results show that the improvement effect and cost of sand-mixed high liquid limit soil reach a comprehensive optimal state when the sand mixing ratio is 20%.